Collective memory and cultural identity: A comparative study of the politics of memory and identity among Israelis of Polish and Tunisian descent - Foscarini, Giorgia (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2017)
The main aim of this article is to provide a preliminary account of the results of my fieldwork research on the identities and memories of the third and fourth generation of Israelis of Ashkenazi and Mizrahi descent, in particular of Polish and Tunisian origin. The issues I will focus on are: “how have third- and fourth-generation Israeli identities been built over time and space?”, and: “how does the current generation of young Israelis relate to their Polish and Tunisian cultural heritage, if at all, in the attempt at understanding and building their present identity?”. The influence of Israel’s historical past and of its migrant memories will be analyzed in relation to the identity-building process of both groups, and to how these memories were integrated, or not, in the Israeli national narrative.